BOOK REVIEWS (Journal of Finance, 1972)
Book reviewed in this article: Macroeconomic Theory and Policy . By W illiam H. B ranson . Money and Banking . By J ohn M. C ulbertson . Monetary and Fiscal Policy in a Growing Economy . By D uncan K. F oley and M iguel S idrauski . The Current Inflation . Edited by H arry G. J ohnson and A. R. N obay . Investment: The Study of an Economic Aggregate . By P hilip J. L und . Money Matters . By A. J ames M eigs . The Business Cycle Today . Edited by V ictor Z arnowitz . Essays in the Theory of Risk‐Bearing . By K enneth J. A rrow . Capital Budgeting: The Public and Private Sectors . By A. J ames B oness . The Repurchase of Common Stock . By C harles D. E llis and A llen E. Y oung . Investment and Portfolio Analysis . By H aim L evy and M arshall S arnat . Monetary Policy and the Federal Funds Market . By J ames M. B oughton . Finance and Economic Development in the Old South: Louisiana Banking 1804–1861 . By G eorge D. G reen . Banking and Economic Development: Some Lessons of History . Edited by R ondo C ameron . The Eurodollar . Edited by H erbert V. P rochnow . Fiscal Federalism . By W allace E. O ates .